Effect of Quartz Content on Physical Parameters of Locally Developed Reactive Powder Concrete - Qureshi, L. A.; Tasaddiq, R. M.; Ali, B.; Sultan, T. (The Nucleus, 2018)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Reactive powder concrete (RPC) belongs to a new category of cement based composites bearing high compressive strength and negligible permeability. The introduction of RPC opened new applications for engineers and researchers specially to be used in nuclear installations. In this research, RPC has been developed first time in Pakistan using locally available ingredients. Present study focused on developing RPC with compressive strength up to 80 MPa because suitable background on RPC was not available in the country. RPC was developed using quartz powder, silica fume, sand, cement, super plasticizer and steel fibers. Different mixes were cast with varying content of quartz powder to check its effect on physical parameters of RPC like compressive strength, tensile strength, modulus of rupture, permeability and uniaxial stress-strain behaviour. The results demonstrated that RPC having compressive strength up to 80 MPa could be produced using materials available in local market. Values of physical parameters increased with the increase in quartz powder content up to a certain limit. After this optimum value, further increase in the quartz powder content caused a decline in the values of different physical parameters studied.